2022
DOI: 10.3390/ani12172257
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare of Fighting Dogs: Wounds, Neurobiology of Pain, Legal Aspects and the Potential Role of the Veterinary Profession

Abstract: Throughout history it has been common to practice activities which significantly impact on animal welfare. Animal fighting, including dogfighting, is a prime example where animals often require veterinary care, either to treat wounds and fractures or to manage pain associated with tissue and where death may even result. Amongst the detrimental health effects arising are the sensory alterations that these injuries cause, which not only include acute or chronic pain but can also trigger a greater sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…The number of businesses that support companion animal ownership, such as grooming, veterinary care, behaviour support and kennels, was also lower in neighbourhoods with a higher animal shelter intake. Studies also identified that neighbourhoods with higher violent crime rates had a higher reported incidence of animal abuse, dangerous animals and illegal dog fighting [ 40 , 41 , 42 , 43 , 44 ]. Dogs involved in organised fights suffer from physical pain and also psychological and emotional distress, indicating that the actions of the guardian can influence the welfare outcomes of the dog [ 41 ].…”
Section: Impact Of the Social Determinants Of Health On Companion Ani...mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of businesses that support companion animal ownership, such as grooming, veterinary care, behaviour support and kennels, was also lower in neighbourhoods with a higher animal shelter intake. Studies also identified that neighbourhoods with higher violent crime rates had a higher reported incidence of animal abuse, dangerous animals and illegal dog fighting [ 40 , 41 , 42 , 43 , 44 ]. Dogs involved in organised fights suffer from physical pain and also psychological and emotional distress, indicating that the actions of the guardian can influence the welfare outcomes of the dog [ 41 ].…”
Section: Impact Of the Social Determinants Of Health On Companion Ani...mentioning
confidence: 99%
“…Studies also identified that neighbourhoods with higher violent crime rates had a higher reported incidence of animal abuse, dangerous animals and illegal dog fighting [ 40 , 41 , 42 , 43 , 44 ]. Dogs involved in organised fights suffer from physical pain and also psychological and emotional distress, indicating that the actions of the guardian can influence the welfare outcomes of the dog [ 41 ]. The quality of infrastructure in a region can have a significant impact on both companion animal and guardian health by influencing the quality of veterinary care.…”
Section: Impact Of the Social Determinants Of Health On Companion Ani...mentioning
confidence: 99%
“…These include a reluctance to address behavioral issues or economic constraints that add to the ethical and legal challenges for the veterinarian [ 19 ]. According to Passantino et al [ 20 ], although these reasons may be relevant for the owner, they cannot be used alone to settle for euthanasia [ 21 , 22 ]. However, a survey performed on 12 dog guardians regarding the consideration of medical treatment or euthanasia of their pet due to age or chronic disease found that persons hesitated in deciding because there is no clear cut-off point to assume by themselves if their dog is in good health without acute clinical signs of an obvious disease.…”
Section: The Euthanasia Process As a Challenging Decision For Veterin...mentioning
confidence: 99%
“…In the United States, the legislation in 42 states (e.g., Alabama, California, Colorado, Connecticut, Florida, Georgia, Maine, New Jersey, Wyoming, among others) justifies the euthanasia of an animal that has caused death or serious injuries, acknowledging them as a potential risk to the civilian population [ 82 , 83 ] and considering euthanasia lawful within the framework of public safety [ 21 ]. The veterinarian’s refusal to perform euthanasia would possibly bring legal or disciplinary consequences because the legislation considers the interests of both the owner of the animal and the general public [ 19 ].…”
Section: Legal Implication For Euthanasia In Chronically Ill Animalsmentioning
confidence: 99%
“…Law enforcement officers frequently disregard this sort of entertainment as well, allowing informal competitions to be organized through breeders' gatherings. Dogfighters have a warped idea of what constitutes fun and find delight in the vicious battles between growling canines (Mota-Rojas et al, 2022).…”
Section: Animal/ Birds Fightermentioning
confidence: 99%